2016
DOI: 10.11604/pamj.2016.24.165.7768
|View full text |Cite
|
Sign up to set email alerts
|

Does gallbladder angle affect gallstone formation?

Abstract: IntroductionMorphology of gallbladder varies considerably from person to person. We believe that one of the morphological variations of gallbladder is the “gallbladder angle”. Gallbladder varies also in “angle”, which, to the best of our knowledge, has never been investigated before. The purpose of this study was to investigate the impact of gallbladder angle on gallstone formation.Methodsin this study, 1075 abdominal computed tomography (CT) images were retrospectively examined. Patients with completely norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…With the aging population, obesity, and hyperlipidemia, the incidence of cholelithiasis has risen to 10% . Normally, genetics, physiology, drugs, and other factors play important roles in the formation and growth of gallstones. , Sanal found that gallstones develop in gallbladders with a smaller angle, perhaps more easily and earlier. Belzer C postulated that calcium precipitation in bile is a critical event in the initiation of cholesterol gallstones.…”
Section: Introductionmentioning
confidence: 99%
“…With the aging population, obesity, and hyperlipidemia, the incidence of cholelithiasis has risen to 10% . Normally, genetics, physiology, drugs, and other factors play important roles in the formation and growth of gallstones. , Sanal found that gallstones develop in gallbladders with a smaller angle, perhaps more easily and earlier. Belzer C postulated that calcium precipitation in bile is a critical event in the initiation of cholesterol gallstones.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies investigated the relationship between the diameter of the ductus cysticus and the angle between the ductus cysticus and the gallbladder with stone formation. Also, studies investigated the anatomical structures and variational developments 6,7,8 . Despite these studies' availability, there are no adequate studies in the literature in recent decades regarding the relationships between biliary canal variations and stone formation.…”
Section: Introductionmentioning
confidence: 99%